L’EFFET DE L’INTERFERENCE D’IGBO SUR D’APPRENTISSAGE DU FRANÇAIS LANGUE ETRANGERE AU NIGERIA - Barine Okoro Diinee; Omodu Darling Jacqueline (American Journals Publishing, 2025)
In the course of this study, we examined the effect of Igbo interference on the learning of French as a foreign language in Nigeria. We studied the types of interferences, those that hinder the learning of French among the students of the University of Port Harcourt, the dangers of interference and measures taken to mitigate such interferences among the Igbo students. We used four objectives and four research questions. Questionnaire was also used to obtain data for the study. At the end of the analysis, we found that interference is a recurring decimal in language studies. The study also showed that grammar, pronunciation, orthography, false friends, etc, are some of the causes of interference.
Keywords: Interference, Igbo, learning, French as a foreign language and teaching.